Left Atrial Dysfunction in the Pathogenesis of Cryptogenic Stroke: Novel Insights from Speckle-Tracking Echocardiography - Leong, Darryl P.; Joyce, Emer; Debonnaire, Philippe; Katsanos, Spyridon; Holman, Eduard R.; Schalij, Martin J.; Bax, Jeroen J.; Delgado, Victoria; Marsan, Nina Ajmone (Journal of the American Society of Echocardiography, 2017)
Myocardial strain analysis by speckle-tracking echocardiography, which can detect subtle abnormalities in left atrial (LA) function, may offer unique insights into LA pathophysiology in patients with cryptogenic stroke (CS). The aim of this study was to investigate whether LA reservoir strain by speckle-tracking echocardiography, as a measure of LA compliance, is impaired in patients with CS and no history of atrial fibrillation. A retrospective case-control study of 742 patients (mean age, 59 ± 13 years; 54% men; 371 with CS and 371 control subjects) was conducted. LA reservoir strain was quantified using speckle-tracking echocardiography. LA strain was significantly lower among patients with CS than control subjects (30 ± 7.3% vs 34 ± 6.7%, P < .001). Current smoking (odds ratio [OR], 2.6; 95% CI, 1.7–4.0; P < .001), systolic blood pressure (OR, 1.17 per 10 mm Hg increase; 95% CI, 1.06–1.29; P = .001), antihypertensive treatment (OR, 0.45; 95% CI, 0.30–0.66; P < .001), larger indexed left ventricular end-systolic volume (OR, 1.04; 95% CI, 1.01–1.07; P = .02), higher E/E′ ratio (OR, 1.06; 95% CI, 1.01–1.11; P = .01), mitral regurgitation (OR, 1.8; 95% CI, 1.2–2.7; P = .003), and lower LA reservoir strain (OR, 1.07 per 1% reduction; 95% CI, 1.05–1.10; P < .001) were independently associated with CS. Importantly, LA reservoir strain conferred incremental discriminatory value in the identification of patients with CS (likelihood ratio P < .001). Subtle LA dysfunction, as assessed by LA reservoir strain with speckle-tracking echocardiography, is associated with CS independent of other cardiovascular risk factors. These findings suggest a potential role for LA strain to risk-stratify patients in the prevention of stroke.